1981
DOI: 10.1038/290413a0
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic facilitation requires paired activation of convergent pathways in the neocortex

Abstract: In associative learning, the activated neurones undergo a variety of concomitant functional alterations--increases or decreases of firing activity and modifications of membrane potential or resistance and of synaptic responsiveness. Synaptic transmission which can be strengthened only when there is paired activity in two pathways is of particular interest in relation to mechanisms for associative learning. For the neocortex, there are few observations of the plastic changes, induced by conditioning procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…3, B and C, qualitatively agree with past electrophysiological results that suggest short microstimulation produces complex and long-lasting effects on cortical networks (Berman et al 1991;Butovas and Schwarz 2003;Butovas et al 2006;Chung and Ferster 1998;Contreras et al 1997;Burkhalter 1996, 1999). We next wanted to further explore the link between our behavioral data, and these other studies by modeling the effect of microstimulation on MT activity that would account for our experimental observations.…”
Section: Modeling the Time Course Of A Single Microstimulation Pulsesupporting
confidence: 80%
See 2 more Smart Citations
“…3, B and C, qualitatively agree with past electrophysiological results that suggest short microstimulation produces complex and long-lasting effects on cortical networks (Berman et al 1991;Butovas and Schwarz 2003;Butovas et al 2006;Chung and Ferster 1998;Contreras et al 1997;Burkhalter 1996, 1999). We next wanted to further explore the link between our behavioral data, and these other studies by modeling the effect of microstimulation on MT activity that would account for our experimental observations.…”
Section: Modeling the Time Course Of A Single Microstimulation Pulsesupporting
confidence: 80%
“…Several studies have previously examined the temporal spread of microstimulation on cortical activity, both in vitro Burkhalter 1996, 1999) and in anesthetized, in vivo preparations (Berman et al 1991;Butovas and Schwarz 2003;Butovas et al 2006;Chung and Ferster 1998;Contreras et al 1997). These studies showed that microstimulation induced long-lasting suppression in neural activity, potentially mediated by GABA B receptor synaptic inhibition (Butovas et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAS-induced changes in MEP amplitude last at least 60 min, are input specific, and are blocked by an NMDA receptor antagonist (Stefan et al, 2000(Stefan et al, , 2002Ridding and Taylor, 2001;Wolters et al, 2003). These characteristics are consistent with the properties of LTP/D as defined in recordings from single neurons or populations of neurons in slice preparations of animal M1 (Baranyi and Feher, 1981;Hess and Donoghue, 1994;Castro-Alamancos et al, 1995;. According to these similarities, the term associative LTP/D-like plasticity was introduced to refer to the PAS-induced changes in MEP amplitude in the human studies (Stefan et al, 2000;Wolters et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, a Hebbian stimulation protocol mimics the synchronization of cortical inputs, from the same or different cortical areas, leading thus to a suprathreshold depolarization of SONs. Studies performed in other brain structures report that non-Hebbian protocols either fail (Baranyi and Fehér, 1981;Gustafsson et al, 1987) or induce plasticity with lower magnitude than Hebbian protocols (Alonso et al, 1990;Urban and Barrionuevo, 1996). Therefore, we investigated whether LTP and LTD induced by Hebbian protocols displayed larger synaptic efficacy changes than those induced by non-Hebbian protocols.…”
mentioning
confidence: 99%